1990
DOI: 10.1002/glia.440030514
|View full text |Cite
|
Sign up to set email alerts
|

Volume‐sensitive release of taurine from cultured astrocytes: Properties and mechanism

Abstract: Release of taurine in response to cell swelling induced by hyposmolarity was observed in cultured astrocytes. Efflux of 3H-taurine increased by 30% and 70% upon reductions in osmolarity of only 5% and 10%. Reductions in osmolarity of 20%, 30%, and 50% stimulated basal taurine release by 300%, 500%, and 1,500%, respectively. The properties of this volume-sensitive release of taurine were examined to investigate: 1) its association with K+ and Cl- fluxes, currently activated during volume regulation: 2) its rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 24 publications
3
60
1
Order By: Relevance
“…Rather, it was postulated that channels may provide a conduit for volume-activated taurine release [14,37,46]. The finding that swelling-induced taurine transport could be inhibited by the stilbene-derivative DIDS prompted the suggestion that the channels could be chloride channels [28,38,47]. Many other studies followed which showed that volume-activated taurine transport could be inhibited by other anion channels blockers.…”
Section: Does Taurine Utilize Volume-activated CL -Channels?mentioning
confidence: 96%
“…Rather, it was postulated that channels may provide a conduit for volume-activated taurine release [14,37,46]. The finding that swelling-induced taurine transport could be inhibited by the stilbene-derivative DIDS prompted the suggestion that the channels could be chloride channels [28,38,47]. Many other studies followed which showed that volume-activated taurine transport could be inhibited by other anion channels blockers.…”
Section: Does Taurine Utilize Volume-activated CL -Channels?mentioning
confidence: 96%
“…9D and (Kimelberg & O'Connor, 1988) and increase of both potassium and chloride permeability (Medrano & Gruenstein, 1993). This depolarization shouldlead to efilux ofK+ from astrocytes, which will antagonize the proposed protective cffect of thesc cells in taking up K+ relcased by neuronal activity, an effect tcrmed 'spatial buffering' (Reichenbach, 1991 (Kimelberg et al 1990b; Pasantes-Morales, Moran & Schousboe, 1990). In cultured cerebrocortical astrocytes it was suggested that the swelling-induced current was cationic (Kimelberg et al 1990a Barres, Chun & Corey, 1990;Ritchie, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Taurine has been shown also to be released from cultured cortical and cerebellar astrocytes in response to swelling following exposure to hyposmotic solution or high extracellular potassium (Pasantes-Morales & Schousboe, 1988Holopainen et al 1989;Martin et al 1990;Kimelberg et al 1990; see Huxtable, 1992). Of particular interest is the response to hyposmotic stimuli, which can occur with minor changes in osmolarity (10-20 mosmol l¢; Martin et al 1990;Pasantes-Morales, Moran & Schousboe, 1990). Taurine is believed to be used by cells as an organic osmolyte to regulate osmotic pressure.…”
Section: Release Of Taurine In Hypotonic Solutionmentioning
confidence: 99%